High fructose corn syrup ınduced liver and heart damage are not reversed with hazelnut consumption: In vivo study - Ayça Toprak-Semiz; Efsane Yavuz-Bedir; Hakan Yüzüak; Murat Usta; Demet Şengül (PLoS ONE, 2025)
Hazelnut, antioxidant, anti-inflammatory effects, has an important role in a healthy diet. High fructose corn syrup (HFCS), used as a sweetener in ready-made food, beverages; causes hyperlipidemia, fatty liver, cardiovascular system damages; oxidative stress, inflammation play role in these damages. Based on these data, we aimed to examine liver and heart damage caused by HFCS in rats and to investigate possible role of hazelnut enriched food in preventing/improving these damages. During this process, weight change, food, liquid consumption were recorded. Biochemical parameters were measured with standard enzymatic techniques. Inflammatory cytokines were determined by ELISA. Liver and heart tissues were evaluated histopathologically, changes were scored, graded. HFCS decreased food, increased liquid consumption. Feeding with hazelnut reduced fluid consumption. HFCS increased weight gain, hazelnut did not reverse it. LDH, CK values increased in HFCS group due to heart damage. While damage occurred in livers of HFCS group due to increased levels of TNF-α and IL-1ß, feeding with hazelnut did not change it. In heart, inflammatory cytokines were similar between groups. In histopathological analysis, inflammation was observed both in livers, hearts of HFCS group. In hazelnut group, a significant decrease in damage was observed compared to HFCS, HFCS+H groups. According to our results, hazelnut supplementation reduced liquid intake and showed limited cardiac protection, but did not reverse HFCS-induced hepatic or cardiac injury.